ASSESS THE KNOWLEDGE ON OBSTETRIC DANGER SIGNS AMONG PREGNANT WOMEN ATTENDING ANTENATAL CARE SERVICE AT SELECTED SETTING - Ezhilarasi S; Kavikuilrani B; RajaRajeshwari S; Prasana S; Reshma S; Rubini T; Ruby G; Sabitha N; Sakthipriya V (The Bioscan, 2025)
Introduction: Obstetric danger signs (ODS) represent critical indicators of potential complications during pregnancy, labor, delivery, and the postpartum period. Common danger signs during pregnancy include severe abdominal pain, vaginal bleeding, blurred vision, and persistent headaches. During labor and delivery, prolonged labor, heavy bleeding, and retained placenta are critical warnings, while postpartum signs include fever, severe bleeding, and foul-smelling discharge. Their recognition by pregnant women and their families is crucial for timely intervention and reducing maternal and neonatal mortality. Methodology: Quantitative approach with non-experimental descriptive research design was chosen. A total of 75 pregnant women were selected through convenient sampling technique. Structured questionnaire was the data collected tool. Results: The study showed that 60% of pregnant women had inadequate knowledge about pregnancy-related complications, with a mean score of 1.6, a median of 1, and a standard deviation of 0.71. Around 33.3% of participants demonstrated a moderate level of knowledge, while only 6.7% had adequate knowledge. The low mean score and high percentage of inadequate knowledge suggest a significant gap in awareness regarding pregnancy-related complications. Conclusion: The study concluded that the pregnant women have a poor knowledge of ODS, the targeted educational intervention is essential to increase the knowledge level and decrease the ratio of maternal death rate among pregnant women.